The comparison of dexmedetomidine and midazolam used for sedation of patients during upper endoscopy: A prospective, randomized study - Yavuz Demiraran; Esin Korkut; Ali Tamer; Ilknur Yorulmaz; Buket Kocaman; Gulbin Sezen; Yusuf Akcan (Canadian Journal of Gastroenterology)
The aim of the present prospective, randomized study was to investigate and compare the safety and efficacy of dexmedetomidine versus midazolam in providing sedation for gastroscopy. A total of 50 adult patients (25 patients receiving dexmedetomidine and 25 patients receiving midazolam), 18 to 60 years of age, and rated I and II on the American Society of Anesthesiologists physical status classification system were included. A brief questionnaire was used to collect demographic data; patients were asked to rate anxiety, satisfaction with care to date and expected discomfort on a visual analogue scale. The following parameters were measured continuously and recorded every minute: heart rate, mean arterial pressure, hemoglobin oxygen saturation and respiratory rate. The two groups were similar with regard to age, body mass index, sex, education, duration of endoscopy, and ethanol or tobacco use. After the procedure, full recovery time, mean arterial pressure, heart rate, respiratory rate and hemoglobin oxygen saturation levels were similiar in both groups. Both groups also had low levels of perceived procedural gagging, discomfort and anxiety scores (P > 0.05), and high satisfaction levels (90.1±3.0 for dexmedetomidine versus 84.9±4.5 for midazolam; P > 0.05). Retching and endoscopist satisfaction were significantly different in patients receiving dexmedetomidine versus those receiving midazolam (88.8±6.5 versus 73.5±16.4,  < 0.05; and 20.6±4.4 versus 45.2±6.0;  < 0.001). In the midazolam group, the number of patients who had adverse effects was higher than the dexmedetomidine group ( < 0.05). As a result, dexmedetomidine performed as effectively and safely as midazolam when used as a sedative in upper gastroscopy; it was superior to midazolam with regard to retching, rate of side effects and endoscopist satisfaction. It was concluded that dexmedetomidine may be a good alternative to midazolam to sedate patients for upper endoscopy.